Communication ICs — market leaders in microelectronics - Stelzer, Andreas; Weigel, Robert (Elektrotechnik und Informationstechnik, 2001)
In recent years communication ICs became the fastest growing semiconductor market segment mainly driven by personal wireless communication products like pagers or mobile phones and internet applications with their permanent demand on increasing bandwidth. The high volume consumer market and its demand for low-cost, low-power, and highly integrated solutions had stimulated RF design engineers all over the world to develop novel integrated solutions for communication devices with an innovative advance that is more close to Moore’s law than it was in the past. This was made possible once by a great progress in semiconductor technology, where well established silicon and silicon bipolar technologies extend the operating range steadily up to higher frequencies in the GHz range at the expense of GaAs technology which is driven back to niche products like power amplifiers and to communication techniques in the 40-Gbits/s range and above. On the other hand the integration of a complete system with a single technology has also consequences to the topology of the system and that has led to fundamental changes in system design procedures, which are treated by more sophisticated design tools which cover both system and circuit design and bring them close together. In this paper some actual trends in the development of communication ICs are presented and examples of recently published devices are given.
elib2cris::1512001600,stelzer2001a
Keywords: circuit-design; development tools; GaAs; bipolar; silicon technology; system development; communication IC; semiconductor industry